Embodied Technology Diffusionand Sectoral Productivity: Evidence for 12 OECD Countries - Thomas Strobel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2013)
International specialization is a strong driver of sectoral productivity. This specialization is not only characterized by the diversity of final goods, but also by the variety of intermediate inputs. Thereby the importance of inputs is not only demonstrated by its large shares in gross output, but also as intermediate inputs constitute important parts of higher value products on later stages of assembly. At that, intermediate inputs encapsulate innovation efforts of upstream sectors facilitating technology diffusion into the widereconomy. Due to the usual assumption of technology being exclusively embodied incapital, this paper analyzes the importance of embodied technology in intermediate inputs as well as the validity of productivity effects stemming from embodied technologydiffusion on sectoral level. Therefore, based on the idea of Romers model of the variety of inputs, two hypotheses are formally tested. The first hypothesis postulates embodied technological change in high-tech inputs, while the second hypothesisassumes that embodied technology diffusion increases aggregate sectoral productivity via use of high-tech inputs. For a sample of 12 OECD countries over the 19952007period, the empirical evidence of this paper shows that there is indeed a bias in technological change toward high-tech inputs and embodied technology diffusion is a source of sectoral productivity increases. However, the effect is more pronounced for goodsproducing sectors than for services.
Keywords: D57; E23; O33; O47; 330; Technology diffusion; augmenting technological change; intermediate inputs; productivity